Long-term Experience of Magnetic Anal Sphincter Augmentation in Patients With Fecal Incontinence. Issue 1 (January 2017) - Sugrue, Jeremy; Lehur, Paul-Antoine; Madoff, Robert D.; McNevin, Shane; Buntzen, Steen; Laurberg, Søren; Mellgren, Anders
Abstract : BACKGROUND: Magnetic anal sphincter augmentation is a novel technique for the treatment of patients with fecal incontinence. OBJECTIVE: The current study reports the long-term effectiveness and safety of this new treatment modality. DESIGN: This was a prospective multicenter pilot study. SETTINGS: The study was performed at 4 clinical sites in Europe and the United States. PATIENTS: The cohort included patients with severe fecal incontinence for ≥6 months who had previously failed conservative therapy and were implanted with a magnetic anal sphincter device between 2008 and 2011. MAIN OUTCOME MEASURES: Adverse events, symptom severity, quality of life, and bowel diary data were collected. RESULTS: A total of 35 patients (34 women) underwent magnetic anal sphincter augmentation. The median length of follow-up was 5.0 years (range, 0–5.6 years), with 23 patients completing assessment at 5 years. Eight patients underwent a subsequent operation (7 device explantations) because of device failure or complications, 7 of which occurred in the first year. Therapeutic success rates, with patients who underwent device explantation or stoma creation counted as treatment failures, were 63% at year 1, 66% at year 3 and 53% at year 5. In patients who retained their device, the number of incontinent episodes per week and Cleveland Clinic incontinence scores significantly decreased from baseline, and there were significant improvements in all 4 scales of the Fecal Incontinence Quality of Life instrument. There were 30 adverse events reported in 20 patients, most commonly defecatory dysfunction (20%), pain (14%), erosion (11%), and infection (11%). LIMITATIONS: This study does not allow for comparison between surgical treatments and involves a limited number of patients. CONCLUSIONS: Magnetic anal sphincter augmentation provided excellent outcomes in patients who retained a functioning device at long-term follow-up. Protocols to reduce early complications will be important to improve overall results.